Personal approach to explore intellectual abilities: Gardner's theory in Educational practice - S A Izumova; Sh I Elnazarova (Peoples' Friendship University of Russia (RUDN University), 2011)
The article reviews the results of formative experiment on the development of different types of intelligence of primary students through new forms and methods of student-centered learning, conducted in line with the scientific direction of Teplov-Nebylitsyn.